MORPHOLOGICAL CHANGES IN KIDNEYS AND CLINICAL PRESENTATION IN PATIENTS WITH PRIMARY AND SECONDARY MEMBRANOUS NEPHROPATHY - Milivojević, Danijel; Pecić, Maja; Nikolić, Gorana; Mioljević, Ana; Brković, Voin; Baralić, Marko; Đurić, Petar; Janković, Aleksandar; Radojević Škodrić, Sanja; Životić, Maja (Srpski medicinski časopis Lekarske komore, 2025)
Introduction/Aim: Membranous nephropathy (MN) typically presents as nephrotic syndrome and may be idiopathic (primary MN, pMN) or occur secondary to other diseases (secondary MN, sMN). Given the differing therapeutic approaches, this study aimed to compare clinical and pathohistological parameters between patients with pMN and sMN. Methods: Through a retrospective analysis of kidney biopsy samples diagnosed at the Institute of Pathology, Faculty of Medicine, Belgrade, between 2011 and 2023, 99 patients with membranous nephropathy were identified. These patients were divided into two groups: patients with pMN (n = 44) and patients with sMN (n = 55). Clinical and pathohistological parameters (by optical and immunofluorescence microscopy) were compared among study participants. Results: While males more frequently suffered from MN, females more frequently had sMN (p = 0.036). Haematuria was more common in subjects with sMN (p = 0.009). Proteinuria values were significantly higher among patients with pMN (p = 0.018), related to a significantly greater decrease in serum total protein values in them (p = 0.011). Endocapillary proliferation was significantly more frequent among those with sMN (p = 0.032). Marked positivity of several immunofluorescent markers was significantly more common in subjects with sMN: IgA, IgM, C1q, κ-chains, and λ-chains (p < 0.050). Conclusion: Females are more commonly affected by sMN. Characteristics of sMN include presence of haematuria, endocapillary hypercellularity and immunofluorescence positivity for markers not seen in pMN (IgA, IgM, C1q), while characteristics of pMN include significantly higher levels of proteinuria, accompanied by significantly reduced serum protein values.